2018
DOI: 10.3928/01477447-20180621-04
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Outcomes of Open Surgery Versus Arthroscopic Surgery for Chronic Refractory Lateral Epicondylitis of the Elbow

Abstract: Numerous surgical options have been introduced for the treatment of chronic refractory lateral epicondylitis of the elbow, but it remains unclear which option is superior. The clinical outcomes of an open surgery group and an arthroscopic surgery group were evaluated, and the results of the 2 procedures were compared. From among patients with lateral epicondylitis refractory to 6 months of conservative treatment, 68 patients satisfying study criteria were recruited. Open surgery was performed in 34 cases (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Klark et al and Kim et al reported that there was no significant difference in DASH score between groups of patients treated with either arthroscopic or open release at 1-2 years follow up. 24,25 As regarding returning to work, the patients after arthroscopic release returned to work earlier than those with open release (5.8 weeks for group-A and 8.8 weeks for group-B) and this was comparable with the results reported by many surgeons. 9,22,[26][27][28][29][30] Care must be taken during arthroscopic tennis elbow release to avoid neurological injuries due to the proximity of important neurological structures especially the ulnar nerve.…”
Section: Discussionsupporting
confidence: 78%
“…Klark et al and Kim et al reported that there was no significant difference in DASH score between groups of patients treated with either arthroscopic or open release at 1-2 years follow up. 24,25 As regarding returning to work, the patients after arthroscopic release returned to work earlier than those with open release (5.8 weeks for group-A and 8.8 weeks for group-B) and this was comparable with the results reported by many surgeons. 9,22,[26][27][28][29][30] Care must be taken during arthroscopic tennis elbow release to avoid neurological injuries due to the proximity of important neurological structures especially the ulnar nerve.…”
Section: Discussionsupporting
confidence: 78%
“…There are very few comparative studies of arthroscopic versus open techniques. [9][10][11][12][13][14][15][16][17] In our review, we found 9 studies that compared arthroscopic and open surgical techniques ( Table 1). The open techniques in these studies were mainly ECRB tenotomy and Nirschl procedure.…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported improvement after surgery for both open and arthroscopic groups. [9][10][11][12][13][14][15][16][17] When comparing the 2 techniques, most authors compared the long-term results, which were overall similar, with minor aberrations. 9,[11][12][13][14][15][16] Stapleton and Baker 9 and Peart et al 11 reported earlier return to work with the arthroscopic group; however, statistical analysis was not done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some surgeons recommend more extensive procedures with simultaneous posterior interosseous nerve decompression and intra-articular pathology resolution [46], and others prefer collateral ligament repair [47]. To reduce the surgical aggressiveness, several arthroscopic extensor tendon release techniques have been introduced [48][49][50] finding that they render equivalent clinical results to the open surgical resection of the same anatomical structures [51,52]. Further refinements are performing the extensor tendon release with an 18-gauge needle [53] or with ultrasound equipment [54].…”
Section: Introductionmentioning
confidence: 99%